The city and its translators : |Istanbul metonymized and refracted in the literary narratives of Ahmet Hamdi Tanpınar and Orhan Pamuk in Turkish, English and French - Ertürk, Şule Demirkol. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
The present thesis explores the relationship between city and text, examining a selection of literary narratives of Istanbul by two main figures of Turkish literature: Ahmet Hamdi Tanpınar and Orhan Pamuk. The selection consists of a section from the Turkish of Tanpınar’s narrative “Istanbul” (1945) from his Bes S ehir (1946) and of a chapter from Pamuk’s Istanbul, Hatıralar ve Sehir (2003) in addition to their translations into English (Five Cities, trans. Ruth Christie, forthcoming; Istanbul, Memoirs and the City, trans. Maureen Freely, 2006) and French (Cinq Villes, Paul Dumont, 1995; Istanbul, souvenirs d’une ville, trans. Jean-François Pérouse, Valérie Gay-Aksoy and Savas Demirel, 2007). In two case studies, following parallel chapters devoted to the contextualization of Tanpınar’s and Pamuk’s narratives, the selected texts are explored and analyzed in depth in three stages. In the first stage, the selected sections in the Turkish of Tanpınar and Pamuk are themselves examined as “translations” of the “text” inscribed in the city, on the assumption that cities can be analyzed as a “discourse” (Barthes, 1985) and read as a “cultural text” (Wirth- Nesher, 1996). In the second stage, the Turkish texts serve as the “source texts” of the interlingual English and French translations that are discussed. A third stage is explored in the analysis of the chapter from Pamuk in which the author not only translates Istanbul but Tanpınar’s version of Istanbul as well, by “translating” Tanpınar as an author, “rewriting” (Tymoczko, 1999a; Lefevere, 1985) him and “refracting” (Lefevere, [1982] 2000; Damrosch, 2003) his authorial identity. Thus, in three stages, the present thesis examines different representations of Istanbul also by foregrounding the “metonymics” of translation (Tymoczko 1999; 2000; Paker 2010a) and the role of all the translators. The choices of the translators of Istanbul are investigated with special emphasis on the translators’ “cognitive states” (Boase- Beier, 2003) and “attitudes” (Hermans, 2007). Based on textual and contextual analyses, this thesis aims to show that Translation Studies provide useful and relevant tools, concepts and methodologies for analyzing literary narratives about cities and their circulation in and between languages and cultures.
Keywords: Translating and interpreting.; Cities and towns in literature.